The Challenges of Using Treffinger Learning Model in Improving Speaking - Akbarani, Rizqi; Putri, Ni Made Anggi Arlina (Institut Agama Islam Negeri Ponorogo, 2022)
Treffinger learning model is one of the cooperative learning models, which allows students to creatively solve problems and encourages their interests in speaking. This research aims to unveil the challenges of using this learning model in improving speaking skill. Drawing on the qualitative data collected through interviews, and observations. This research found that unveiled that students’ lack of motivation, ability in English, teachers’ readiness, and time made it difficult for the application of the Treffinger learning model.